Republic of Tajikistan : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Waiver of Nonobservance of Performance Criteria, and Request for Modification of Performance Criteria: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Tajikistan. (IMF Staff Country Reports; Country Report ;, 2012)
Economic activity in Tajikistan continues to recover from the global crisis, but a range of vulnerabilities remain. Real GDP grew at an estimated 7.5 percent through the first nine months of 2011. The political environment appears broadly stable, but there are underlying tensions. The worst of the food and fuel price shocks has been weathered without civil unrest, partly owing to measures to ensure supplies, higher remittances, and a general understanding by the population that remedies are limited given resource constraints.